KONSELING KESEHATAN MENTAL: SOLUSI MODERN UNTUK MEMBANTU INDIVIDU BERTAUBAT - Muttaqin, Reza; Fauziah, Mira; Zalikha, Zalikha; Jarnawi, Jarnawi (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
Research shows that repentance can help individuals overcome various mental health problems, such as anxiety, depression, and guilt. Mental health counseling can play an important role in increasing awareness of repentance and assisting individuals in the process of repentance. Purpose of the Study This study aims to understand the role of mental health counseling in increasing awareness of repentance in Islam. This study uses a library research method by reviewing literature related to repentance, mental health, and counseling in the context of Islam. The data sources used include books, scientific journals, and scientific articles. The results of the study indicate that repentance and mental health have a close relationship. Repentance can help individuals achieve optimal mental health, and mental health counseling can assist individuals in the process of repentance. Mental health counseling can help individuals by: Assessing the individual's psychological condition, providing appropriate counseling and guidance services, helping individuals understand the root of their problems, increasing individual self-awareness, developing individual coping skills, strengthening individual faith, helping individuals to make a repentance plan. Conclusion, repentance and mental health counseling are two important elements in achieving optimal mental and spiritual health. By combining the two, individuals can find solutions to the psychological problems they face and live a more positive and meaningful life